If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + 13 = 2x + 153 Reorder the terms: 13 + 12x = 2x + 153 Reorder the terms: 13 + 12x = 153 + 2x Solving 13 + 12x = 153 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 13 + 12x + -2x = 153 + 2x + -2x Combine like terms: 12x + -2x = 10x 13 + 10x = 153 + 2x + -2x Combine like terms: 2x + -2x = 0 13 + 10x = 153 + 0 13 + 10x = 153 Add '-13' to each side of the equation. 13 + -13 + 10x = 153 + -13 Combine like terms: 13 + -13 = 0 0 + 10x = 153 + -13 10x = 153 + -13 Combine like terms: 153 + -13 = 140 10x = 140 Divide each side by '10'. x = 14 Simplifying x = 14
| 9+12x=108+x | | 108-4x=23x+18 | | 5x-1=12x-71 | | 6y+12x= | | 7-7x=85-21x | | y=-10x+2 | | -79-9x=10x+16 | | 5(2c-3)-9c-4= | | 7z-19z=108 | | 2x+14=-49-7x | | 14x+-14x= | | 143-5x=5x+23 | | 72-4x=7x+17 | | 72-7x=11x+16 | | 13-9x=65-37x | | 7+4x=28+x | | 2x+11=-29-8x | | 85-2x=3x+10 | | -14-3x=6-8x | | 2x+8y=-3 | | 4x+33=12x-39 | | 4x+33=12x-64 | | 3(5x+2)=66 | | 7x-4y=21 | | 3x+5=61-5 | | 3+3x=27+x | | 115-2x=25x+16 | | 6x-1=16x-121 | | 4x+32=14x-58 | | 2x+46=7x-14 | | 10-9X=205-44X | | 6x+36=8x+12 |